(untitled) (Revista Lusófona de Educação, 2020)
Ana Paiva, Full Professor in the Department of Computer Engineering at Instituto Superior Técnico (IST), University of Lisbon and coordinator of the GAIPS group at INESC-ID talks with Conceição Costa, MILT coordinator and Principal Investigator at CICANT - Universidade Lusófona de Humanidades e Tecnologias about peer learning with robots.